Mark an introduction and study guide : shaping the life and legacy of Jesus - Smith, Abraham (London Bloomsbury T&T Clark, 2017)
Introduction: Reshaping the memory of a teacher and his movement -- Mark as a life about Jesus -- Mark as a life for Jesus' followers -- Jesus as a prophetic envoy -- Jesus as a powerful broker -- Jesus as a philosophical hero
First published 2015 (Sheffield: Sheffield Phoenix Press). - Includes bibliographical references and indexes
Keywords: Jesus Christ -- Biography; Jesus Christ -- Biography -- Jesus Christ; Bible -- Criticism, interpretation, etc; Bible -- Criticism, interpretation, etc -- Bible